ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS I C DI MI SALAFIYAH TUGUNG SEMPU BANYUWANGI - Ramiati, Eka; Sa'idatul Humairoh, Siti; Faizah, Kurniyatul (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
Based on research conducted at MI Salafiyah Tugung Sempu, several students still face difficulties in reading, particularly in Class I C. Out of 23 students, 5 have not yet achieved adequate reading skills. These difficulties are influenced by factors stemming from both the students themselves and external factors. This study aims to describe (1) the types of reading difficulties encountered by Class I C students at MI Salafiyah Tugung Sempu and (2) the factors hindering early reading skills among these students. The study uses a qualitative approach with a case study methodology. The selection of the subject class was based on considerations by the class teacher. The subjects of this study were students in Class I C in the second semester of the 2023/2024 academic year, specifically 4 male students and 1 female student who had low reading ability and were categorized as having reading difficulties, as well as their teacher and parents. The results of the study indicate that students experience challenges in connecting letters into words and words into meaningful sentences, as well as in using appropriate punctuation. Contributing factors in this study include a lack of interest and motivation to read, limited facilities and learning media at home, and insufficient support and reading practice in the home environment. Based on these findings, there is a need for more engaging and interactive teaching strategies to increase students' interest in reading. Furthermore, stronger parental support and the provision of adequate facilities and learning media at home are also key to overcoming these initial reading difficulties. With an integrated approach and comprehensive support from various stakeholders, students are expected to develop good reading habits and enhance their overall reading abilities.